Visions of empire in the Nazi-occupied Netherlands - Foray, Jennifer L., 1976- (Cambridge University Press, 2012)
"Visions of Empire in the Nazi-Occupied Netherlands is both a political history of the Nazi-occupied Netherlands and a study of empire, occupation, and decolonization"--